Повести - Отрошенко Владислав Олегович (Логосвос, 2023)
Источник записи: Москва: ЛитРес : Самиздат, 2016 Экземпляры: БС (20240904) / Инвентарный номер: ФЖД13371 / Сис.шифр: 84(2) / Авт.знак: О-86 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4